Expression of lncRNAs in response to bacterial infections of goat mammary epithelial cells reveals insights into mammary gland diseases. (January 2022) - Mumtaz, Peerzada Tajamul; Taban, Qamar; Bhat, Basharat; Ahmad, Syed Mudasir; Dar, Mashooq Ahmad; Kashoo, Zahid Amin; Ganie, Nazir A.; Shah, Riaz Ahmad
Abstract: Mastitis or inflammation of the mammary gland is a highly economic and deadly alarming disease for the dairy sector as well as policymakers caused by microbial infection. Transcriptomic and proteomic approaches have been widely employed to identify the underlying molecular mechanisms of bacterial infections in the mammary gland. Numerous differentially expressed mRNAs, miRNAs, and proteins together with their associated signaling pathways have been identified during bacterial infection, paving the way for analysis of their biological functions. Long noncoding RNAs (lncRNAs) are important regulators of multiple biological processes. However, little is known regarding their role in bacterial infection in mammary epithelial cells. Hence, RNA-sequencing was performed by infecting primary mammary epithelial cells (pMECs) with both gram-negative ( E. coli ) and gram-positive bacteria ( S. aureus ). Using stringent pipeline, a set of 1957 known and 1175 novel lncRNAs were identified, among which, 112 lncRNAs were found differentially expressed in bacteria challenged PMECs compared with the control. Additionally, potential targets of the lncRNAs were predicted in cis- and trans- configuration. KEGG analysis revealed that DE lncRNAs were associated with at least 15 immune-related pathways. Therefore, our study revealed that bacterial challenge triggers the expression of lncRNAs associated with immune response and defense mechanisms in goat mammary epithelial cells. Highlights: Mammary gland infections in cattle are deadly alarming disease with huge economic impact. It has severe effect on epithelial tissue damage, induced either by apoptosis or necrosis. Here in this study we used pMECs as the model cells to study the role of lncRNAs in mammary gland infections by challenging with two major pathogens viz E. coli and S. aureus involved in udder infections. Using RNA sequencing we cataloged novel DE lncRNAs not yet known to be associated with bacterial infections, thereby opening new insights into mammary gland infections. A set of 1957 known and 1175 novel lncRNAs were identified, among which, 112 lncRNAs were found differentially expressed in bacteria challenged PMECs compared to their controls.